ANALISIS PERAN GURU DALAM MENANAMKAN GROWTH MINDSET PADA PEMBELAJARAN MATEMATIKA SISWA KELAS IV SDN TEGALGANDU 02 - Aji, Saefulloh; Nurpratiwiningsih, Laelia; Moh. Toharudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of teachers in instilling growth mindset in fourth-grade mathematics learning at SDN Tegalgandu 02, Brebes Regency, Central Java. Qualitative research with a case study design was employed. Data were collected through in-depth interviews with the fourth-grade classroom teacher and students, participatory observation, and documentation review of learning instruments. Data validity was ensured through source and technique triangulation and analyzed using the Miles and Huberman interactive model. Three main findings emerge. First, the growth mindset profile of fourth-grade students shows significant variation: some students demonstrate perseverance and openness to challenge, while students with lower ability still exhibit fixed mindset patterns marked by math anxiety and a tendency to give up when facing complex story problems. Second, the teacher plays a strategic role through three key instructional strategies: graduated challenge by designing tiered-difficulty tasks; process praise by appreciating effort and problem-solving strategies rather than only correct final answers; and normalization of mistakes by building an error-friendly classroom environment where errors serve as collective learning opportunities. Third, the main obstacles include the wide gap in students' initial abilities, limited instructional time under the Merdeka Curriculum, and negative family influence that reinforces fixed mindset at home. The teacher responds with individual humanistic approaches, simplification of problem instructions, concrete media, and peer tutoring in heterogeneous groups. These findings confirm that the teacher's role as a humanistic facilitator is the central axis in building students' cognitive resilience in elementary mathematics learning